2001
DOI: 10.1016/s0735-1097(01)01311-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced silent myocardial ischemia and coronary morbidity and mortality in middle-aged men

Abstract: Exercise-induced silent myocardial ischemia was a strong predictor of CHD in men with any conventional risk factor, emphasizing the importance of exercise testing to identify asymptomatic high risk men who could benefit from risk reduction and preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 37 publications
3
77
1
5
Order By: Relevance
“…Other studies have shown the presence of silent ischemia to be predictive of the advent of angina rather than death or MI 19 and that the coexistence of at least one conventional risk factor in addition to ST depression substantially increases the relative risk of coronary events. 86 …”
Section: Cohn Et Al Silent Myocardial Ischemiamentioning
confidence: 99%
“…Other studies have shown the presence of silent ischemia to be predictive of the advent of angina rather than death or MI 19 and that the coexistence of at least one conventional risk factor in addition to ST depression substantially increases the relative risk of coronary events. 86 …”
Section: Cohn Et Al Silent Myocardial Ischemiamentioning
confidence: 99%
“…This observation was made by using a maximal symptom-limited E-ECG stress test in 1769 middle-aged men. 9 In a previous article, our group also showed the usefulness of E-ECG for predicting CHD in patients with DM. We observed 2854 men with DM who completed a maximal E-ECG test and were without a previous CVD event at baseline.…”
Section: Discussionmentioning
confidence: 87%
“…Our results concerning the positive association between abnormal E-ECG results and a higher risk of CHD mortality are in unison with other population-based studies of asymptomatic men with other CVD risk factors. 9,[20][21][22] The Framingham Heart Study-Offspring found that ST-segment depression provided additional prognostic information in age-and Framingham risk score-adjusted models in men, particularly among those in the highest-risk group (10-year predicted CHD risk of ≥20%). 20 This study evaluated 3043 asymptomatic men and women, who underwent a symptom-limited E-ECG test and were followed up for 18.2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations